1999
DOI: 10.1002/hep.510290104
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Adenosine in Inducing Nitric Oxide Synthesis in Rat Liver Ischemia Preconditioning Is Mediated by Activation of Adenosine A2 Receptors

Abstract: This study aims to determine if the protective role of adenosine in liver ischemic preconditioning is mediated by the activation of adenosine receptors and to ascertain which of these receptors is implicated in the process. Administration of adenosine A 1 and A 2 receptor antagonists to preconditioned animals indicates that hepatic preconditioning is mediated by the activation of adenosine A 2 receptors. Propentofylline (an inhibitor of adenosine transport into cells) in the preconditioned group, subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
170
5
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(192 citation statements)
references
References 24 publications
14
170
5
3
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18]24 Although little is known about the molecular basis of the preconditioning, oxidative stress seems to be one of the causes. Peralta et al 15,25 and Yin et al 26 have reported the role of nitric oxide and free radicals during ischemic preconditioning in the liver. In addition, HSPs induced by the stresses may also play a critical role for the subsequent hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18]24 Although little is known about the molecular basis of the preconditioning, oxidative stress seems to be one of the causes. Peralta et al 15,25 and Yin et al 26 have reported the role of nitric oxide and free radicals during ischemic preconditioning in the liver. In addition, HSPs induced by the stresses may also play a critical role for the subsequent hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments, mainly performed in the heart, suggest a number of substances as potential ligands, including adenosine, bradykinin, catecholamines, reactive oxygen species, opiods, angiotensin II, and NO [68]. With regard to the liver, adenosine has thus far been considered the major player in triggering preconditioning [62,63,65,69,70]. Adenosine is a breakdown product of ATP that is released in large quantities into the extracellular space within seconds of the onset of ischemia.…”
Section: Protective Mechanisms Of Early Ischemic Preconditioningmentioning
confidence: 99%
“…A 1 and A 2 receptors have been chiefly implicated in the ischemic preconditioning of the myocardium and liver, respectively [62,63,65,69,71].…”
Section: Protective Mechanisms Of Early Ischemic Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Peralta and colleagues has shown that adenosine is implicated in liver preconditioning by stimulating NO generation. 4,11,12 In isolated hepatocytes we have observed that the treatment with 4-phorbol-12-myristate-13-acetate (PMA) or with 1,2 dioctanoyl-glycerol mimics the effects of preconditioning. 8 Conversely, the PKC inhibitor chelerythrine abolishes the citoprotection, 8 suggesting that PKC activation might play a role in liver preconditioning.…”
mentioning
confidence: 99%